Magnetic Behavior of mnps3 Phases Intercalated by [Zn 2l]2 lh2 Macrocyclic Ligand Obtained by Condensation of 2-Hydroxy-5-Methyl-1,3-Benzenedicarbaldehyde and 1,2-Diaminobenzene) - Venegas-Yazigi, D; Venegas-Yazigi, D (2011)
The intercalation of the cationic binuclear macrocyclic complex [Zn 2L]2 (LH2: macrocyclic ligand obtained by the template condensation of 2-hydroxy-5-methyl-1,3-benzenedicarbaldehyde and 1,2-diaminobenzene) was achieved by a cationic exchange process, using K 0.4Mn0.8PS3 as a precursor. Three intercalated materials were obtained and characterized: (Zn2L) 0.05K0.3Mn0.8PS3 (1), (Zn 2L)0.1K0.2Mn0.8PS3 (2) and (Zn2L)0.05K0.3Mn0.8PS 3 (3), the latter phase being obtained by an assisted microwave radiation process. The magnetic data permit to estimate the Weiss temperature ? of ?-130 K for (1); ?-155 K for (2) and ?-130 K for (3). The spin canting present in the potassium precursor remains unperturbed in composite (3), and spontaneous magnetization is observed under 50 K in both materials. However composites (1) and (2) do not present this spontaneous magnetization at low temperatures. The electronic properties of the intercalates do not appear to be significantly altered. The reflectance spectra of the intercalated phases (1), (2) and (3) show a gap value between 1.90 and 1.80 eV, lower than the value observed for the K0.4Mn0.8PS3 precursor of 2.8 eV. © 2011 Elsevier Inc. All rights reserved.